Attentional control in the attentional blink is modulated by odor - Colzato, Lorenza S.; Sellaro, Roberta; Rossi Paccani, Claudia; Hommel, Bernhard (Attention, perception & psychophysics, 2014)
Increasing evidence suggests that `aromas have distinctive effects on the allocation of attention in space: Arousing olfactory fragrances (e.g., peppermint) are supposed to induce a more focused state, and calming olfactory fragrances (e.g., lavender) a broader attentional state. Here, we investigate whether odors have similar effects on the allocation of attention in time. Participants performed the attentional blink (AB) task, known to produce a deficit in reporting the second of two target stimuli presented in close succession in a rapid sequence of distractors, while being exposed to either a peppermint or a lavender aroma. In two experiments using a between-subjects and a within-subjects design, respectively, we show that the two odors have specific effects on attentional control: As compared with the calming lavender aroma, the arousing peppermint condition yielded a larger AB. Our results demonstrate that attentional control is systematically modulated by factors that induce a more or a less distributed state of mind.